2014
DOI: 10.1111/jnc.12947
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces phosphorylation of the AMPA receptor subunit GluR1, reversed by ZIP, and over‐expression of Protein Kinase M zeta, reversed by amyloid beta

Abstract: Insulin receptor (IR) in the brain plays a role in synaptic plasticity and cognitive functions. Phosphorylation of a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors GluR1 subunit at Serine 831 is regulated by calcium-calmodulindependent protein kinase II and protein kinase C that underlie long-term potentiation and learning/memory. Recent studies have shown that the novel Protein Kinase M zeta (PKMf) underlies synaptic plasticity and may regulate AMPAr. In this study, we show that insulin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…It is thought to be more powerful in destructing the physiology of learning and memory. Thus, it is thought that soluble Aβ oligomers could be the "initiation factor" of AD in the early stages of AD pathology [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…It is thought to be more powerful in destructing the physiology of learning and memory. Thus, it is thought that soluble Aβ oligomers could be the "initiation factor" of AD in the early stages of AD pathology [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms are complex. It is found that insulin can activate α-amino-3-hydroxy-5-methyl-4- isoxazolepropionic acid (AMPA) receptors and leads to increased hippocampal long-term potentiation (LTP; Adzovic and Domenici, 2014). Another mechanism involving insulin modulated cognition is via inflammation pathway.…”
Section: Gut Dysbacteriosis Contributes To DCImentioning
confidence: 99%
“…). AMPARs also appear to influence β‐amyloid‐related processing: recently a new intracellular insulin signalling pathway was described involving glutamate R1 subunit‐containing AMPARs which influenced the production and accumulation of β‐amyloid (Adzovic and Domenici ). AMPAR up‐regulation has been proposed to be a link to locomotor sensitization and enhanced drug seeking behaviour (Boudreau et al .…”
Section: Amino Acid‐mediated Transmission Signalling and Pathobiologymentioning
confidence: 99%